1987
DOI: 10.1152/ajpendo.1987.253.2.e179
|View full text |Cite
|
Sign up to set email alerts
|

Cold exposure potentiates the effect of insulin on in vivo glucose uptake

Abstract: The effects of cold exposure (48 h at 4 degrees C) and insulin injection (0.5 U/kg iv) on the rates of net 2-[3H]deoxyglucose uptake (Ki) in peripheral tissues were investigated in warm-acclimated rats (25 degrees C). Cold exposure and insulin treatment independently increased Ki values in skeletal muscles (soleus, extensor digitorum longus, and vastus lateralis), heart, white adipose tissue (subcutaneous, gonadal, and retroperitoneal), and brown adipose tissue (P less than 0.01). The effects of cold exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
54
1
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 25 publications
10
54
1
2
Order By: Relevance
“…It seems, therefore, most likely that the increased GLUT4 contents account for the improved sensitivity of glucose transport to insulin. In accordance with this, it has been reported that the increased GLUT4 expression in BAT under cold environment is associated with potentiation of the insulin effect on glucose uptake in vivo [33].…”
Section: Discussionsupporting
confidence: 77%
“…It seems, therefore, most likely that the increased GLUT4 contents account for the improved sensitivity of glucose transport to insulin. In accordance with this, it has been reported that the increased GLUT4 expression in BAT under cold environment is associated with potentiation of the insulin effect on glucose uptake in vivo [33].…”
Section: Discussionsupporting
confidence: 77%
“…Studies of insulin production and action and of glucose uptake in homeothermic animals exposed to cold revealed that, in this particular physiological condition, glucose is efficiently mobilized, despite low blood insulin levels and an apparent tissue-specific resistance to insulin's action (7,11,41,45). Therefore, it became clear that mechanisms that act independently of insulin signaling through the IR-IR substrates (IRSs)-Akt pathway play an important role in the control of glucose disposal in coldexposed animals.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of homeothermic animals to a cold environment has been widely used as a model for studying glucose homeostasis and insulin action (11,45). Under this condition, animals mobilize glucose more efficiently, despite molecular resistance to insulin signal transduction in skeletal muscle and adipose tissue (11).…”
mentioning
confidence: 99%
“…The work of others has demonstrated a marked increase in the sensitivity to insulin induced by cold-exposure (Vallerand et al, 1986(Vallerand et al, , 1987Bartness et al, 1986aBartness et al, , 1986b. Cold-exposure potentiates the effect of insulin on in vivo glucose uptake in BAT at a normal insulin level, and glucose would principally be utilized in de novo lipogenesis as fuel for BAT thermogenesis.…”
mentioning
confidence: 98%